2013
DOI: 10.1007/s00244-013-9981-6
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Toxicity of SN2-Reactive Soft Electrophiles: 3. Evaluation of Ethyl α-Halogenated Acetates with α-Halogenated Acetonitriles

Abstract: Mixture toxicity for each of four ethyl α-halogenated acetates (ExACs) with each of three α-halogenated acetonitriles (xANs) was assessed. Inhibition of bioluminescence in Vibrio fischeri was measured after 15, 30 and 45-min of exposure. Concentration-response curves were developed for each chemical at each exposure duration and used to develop predicted concentration-response curves for the dose-addition and independence models of combined effect. Concentration-response curves for each mixture and each exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 15 publications
4
24
0
Order By: Relevance
“…These data support the hypothesis that the soft electrophiles in this DBP mixture have a cumulative toxicity and support previous findings of dose additivity in S N 2-reactive electrophiles. 1214 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data support the hypothesis that the soft electrophiles in this DBP mixture have a cumulative toxicity and support previous findings of dose additivity in S N 2-reactive electrophiles. 1214 …”
Section: Resultsmentioning
confidence: 99%
“…911 Dawson et al investigated cumulative toxicity of S N 2-reactive haloacetonitriles (HANs) and ethyl- α -halogenated acetates and reported some instances of dose additive toxicity within and among these chemical classes. 1214 The electrophiles within these classes reacted with glutathione (GSH) in chemico ; the reported dose additive toxicity may be attributed to collective GSH depletion as a shared mechanism or molecular initiating event (MIE). 1214 Investigating S N 2-reactive compounds or GSH-depleting agents as a CMG may aid in evaluating additive toxicity within complex DBP mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, experiments with α,β-unsaturated carbonyl derivatives, showed additive toxicity in binary and ternary mixtures in vitro and in an in vivo model (Zhang et al, 2016). Work by Dawson and colleagues showed that HANs and halogenated ethyl acetates (α-halogenated carbonyl containing compounds) generated, in some cases, dose additive toxicity within and among these chemical classes (Dawson et al, 2010; Dawson et al, 2011; Dawson et al, 2014). Additive genotoxicity was observed in binary mixtures of BAM and BAN (Pals et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have examined toxicity of selected mixtures of industrial organic chemicals (e.g., Gagan et al 2007, Dawson et al 2008), developed and evaluated the 5PL-1P function for concentration-response curve-fitting (Dawson et al 2012, 2016) and examined the viability of using time-dependent toxicity (TDT) of the individual chemicals for predicting TDT of the mixtures (Dawson et al 2014a). The design of these studies has included multiple tests of individual chemicals (Dawson et al 2010, 2011, 2014b, 2016) thereby allowing for assessment of test-to-test consistency of those data, but none of these studies had evaluated such consistency over several tests of the same mixture. For this system to be a reliable approach for evaluating mixture toxicity of commonly used industrial organics such an assessment was needed.…”
Section: Introductionmentioning
confidence: 99%